Multi-factor, multi-state, multi-model scenarios: Exploring food and climate futures for Southeast Asia - Mason-D'Croz, Daniel; Vervoort, Joost M.; Palazzo, Amanda; Islam, Shahnila; Lord S; Helfgott, Ariella E.S.; Havlík, Petr; Peou, Rathana; Sassen, M.; Veeger, Marieke; Soesbergen, Arnout van; Arnell, A.P.; et al. (Elsevier, 2016)
Decision-makers aiming to improve food security, livelihoods and resilience are faced with an uncertain future. To develop robust policies they need tools to explore the potential effects of uncertain climatic, socioeconomic, and environmental changes. Methods have been developed to use scenarios to present alternative futures to inform policy. Nevertheless, many of these can limit the possibility space with which decision-makers engage. This paper will present a participatory scenario process that maintains a large possibility space through the use of multiple factors and factor-states and a multi-model ensemble to create and quantify four regional scenarios for Southeast Asia. To do this we will explain 1) the process of multi-factor, multi-state building was done in a stakeholder workshop in Vietnam, 2) the scenario quantification and model results from GLOBIOM and IMPACT, two economic models, and 3) how the scenarios have already been applied to diverse policy processes in Cambodia, Laos, and Vietnam.